Association between monocyte-lymphocyte ratio and all-cause and cardiovascular mortality in patients with chronic kidney diseases: A data analysis from national health and nutrition examination survey (NHANES) 2003-2010 - Wenwu Liu; Shuwei Weng; Chenghui Cao; Yuting Yi; Yue Wu; Daoquan Peng (Renal Failure)
Background The relationship between monocyte-to-lymphocyte ratio (MLR) and prognosis in patients with chronic kidney disease (CKD) remains unclear. The aim of this study was to investigate the association between MLR and both all-cause mortality and cardiovascular disease (CVD) mortality in patients with CKD.Methods This study analyzed data from National Health and Nutrition Examination Survey 2003-2010. This study included 11262 eligible subjects, and 3015 of them were with CKD. We first compared the differences in clinical characteristics between individuals with and without CKD, and then grouped the CKD population based on quartiles of MLR. The partial correlation analysis was conducted to assess the relationships between MLR and some important clinical features. Cox proportional hazards models were used to investigate the associations between MLR and mortality from all-cause and cardiovascular disease. Restricted cubic spline (RCS) was used to investigate the dose-response relationship between MLR and mortality, the receiver operating characteristic (ROC) curves is used to compare the efficacy of MLR with different clinical biological indicators in assessing the risk of death.Results During a median follow-up of 10.3 years in CKD population, 1398 (43%) all-cause deaths and 526 (16%) CVD deaths occurred. It has been found that individuals with CKD have higher MLR level. The partial correlation analysis results showed that even after adjusting for age, sex, and race, MLR is still correlated with blood glucose, lipid levels, and kidney function indicators. The results of the cox proportional hazards regression model and Kaplan-Meier curve shown after adjusting for covariates, higher MLR was significantly associated with an increased risk of mortality. Consistent results were also observed when MLR was examined as categorical variable (quartiles). The RCS demonstrated a positive association between MLR and the risk of all-cause mortality and cardiovascular mortality. The ROC results indicate that the predictive efficacy of MLR for all-cause mortality risk is comparable to eGFR, higher than NLR and CRP. The predictive efficacy of MLR for cardiovascular mortality risk is higher than these three indicators.Conclusion Compared to non-CKD population, the CKD population has higher levels of MLR. In the CKD population, MLR is positively correlated with the risk of death. Furthermore, the predictive efficacy of MLR for mortality risk is higher than other clinical indicators. This suggests that MLR can serve as a simple and effective clinical indicator for predicting mortality risk in CKD patients.